Is the combination of depression symptoms and multimorbidity associated with the increase of the prevalence of functional disabilities in Brazilian older adults? A cross-sectional study - Rosa, Patrícia Pereira de Souza da; Marques, Larissa Pruner; Corrêa, Vanessa Pereira; De Oliveira, Cesar; Schneider, Ione Jayce Ceola (Frontiers in Aging, 2023)
Introduction: Functional disabilities are more prevalent in older adults with multimorbidity and depression. However, few studies have investigated the combination of multimorbidity and depression with functional disability. This study aims to verify whether symptoms of depression and multimorbidity combined increase the prevalence of functional disability in Brazilian older adults. Material and methods: This is a cross-sectional study conducted with data from the Brazilian Longitudinal Study of Aging (ELSI-Brazil) baseline examination in 2015–2016 in adults aged 50 years and older. The variables included were basic (BADL) and instrumental activities of daily living (IADL), depressive symptoms, multimorbidity (≥2 chronic diseases), sociodemographic variables, and lifestyle. Logistic regression was performed to estimate crude and adjusted odds ratios. Results: A total of 7,842 participants over 50 years of age were included. Of these, 53.5% were women and 50.5% were between 50 and 59 years old, 33.5% reported ≥4 depressive symptoms, 51.4% had multimorbidity, 13.5% reported difficulty in performing at least one BADL, and 45.1% reported difficulty in performing the IADL. In the adjusted analysis, the prevalence of difficulty on BADL was 6.52 (95% CI: 5.14; 8.27) and on IADL was 2.34 (95% CI: 2.15; 2.55), higher for those with depression and multimorbidity combined when compared with those without these conditions. Conclusion: The combination of symptoms of depression and multimorbidity may increase functional impairments in the BADL and IADL of Brazilian older adults, impairing self-efficacy, independence, and autonomy. Early detection of these factors benefits the person, their family, and the healthcare system for health promotion and disease prevention.